1989
DOI: 10.1111/j.1752-7325.1989.tb02070.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Saskatchewan Pit and Fissure Sealant Program: a Longitudinal Followup

Abstract: The Saskatchewan Health Dental Plan (SHDP) is a publicly funded dental insurance program for children between the ages of five and 16 years residing in the province. In 1981, fissure sealants were added as a covered expense. Until September 1, 1987, sealants and other dental treatments covered under the SHDP were provided to schoolchildren by dental therapists in dental clinics established in elementary schools throughout the province. After September 1, 1987, the provision of dental services was transferred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
3
8
0
1
Order By: Relevance
“…This confirms the continued effectiveness of the dental preventive programme for permanent teeth, even though this is less than that reported in evaluations carried out after 2 and 4·5 years into the programme [33,34]. Results after 7·5 years show benefit with reductions in DMFT, DMFM and DMFS comparable to those seen in other studies carried out in areas with dental‐health programmes [4,5,35–37].…”
Section: Discussionsupporting
confidence: 74%
“…This confirms the continued effectiveness of the dental preventive programme for permanent teeth, even though this is less than that reported in evaluations carried out after 2 and 4·5 years into the programme [33,34]. Results after 7·5 years show benefit with reductions in DMFT, DMFM and DMFS comparable to those seen in other studies carried out in areas with dental‐health programmes [4,5,35–37].…”
Section: Discussionsupporting
confidence: 74%
“…In 1981, pit and fissure sealants were added to the services provided by the SHDP. Seventy‐nine percent of sealants completed were retained 3 years after placement . Sealed teeth experienced 46 percent fewer carious lesions than unsealed teeth 4 years after placement.…”
Section: Dental Plan Results 1974–87mentioning
confidence: 99%
“…A meta-analysis carried out by Llodra et al showed that the overall effectiveness of autopolymerized resin was 71 percent and the authors concluded t ha t " auto p ol y mer izing s e a 1 an t s should be used" (24). IsmaiI and coworkers reported in an evaluation of the Saskatchewan dental program that sealed teeth experienced 46 percent fewer carious lesions than unsealed teeth four years after the application of sealants (25).…”
Section: Discussionmentioning
confidence: 99%